Key elements in the naturalisation of neoliberal discourse in higher education in Chile. Issue 4 (3rd July 2020) - Simbürger, Elisabeth; Donoso, Alina
ABSTRACT: Neoliberal discourse has undergone substantial changes over the last years, taking a status as if it were a natural given. In this article we analyse the naturalisation of neoliberal discourse in higher education in post-dictatorship Chile. Based on discourse analysis of two Chilean higher education policy reports, we examine the reconfiguration of the dimensions of the public and the private and identify three discursive prerequisites for the naturalisation of neoliberalism in Chilean higher education: first, the silencing of the dictatorial origins of the system; second, the idea of neutrality as a means to present public and private higher education as if they were equal; and third, the role of social democracy in a 180 degrees' inversion of meanings of the public and the private. We finally look into recent developments in Chilean society such as the Chilean students' movement from 2011 that triggered the questioning of the naturalisation of neoliberal discourse.